A comparison of trunk biomechanics, musculoskeletal discomfort and productivity during simulated sit-stand office work. Issue 10 (2nd October 2016) - Karakolis, Thomas; Barrett, Jeff; Callaghan, Jack P.
Abstract: Sedentary office work has been shown to cause low back discomfort and potentially cause injury. Prolonged standing work has been shown to cause discomfort. The implementation of a sit–stand paradigm is hypothesised to mitigate discomfort and prevent injury induced by prolonged exposure to each posture in isolation. This study explored the potential of sit–stand to reduce discomfort and prevent injury, without adversely affecting productivity. Twenty-four participants performed simulated office work in three different conditions: sitting, standing and sit–stand. Variables measured included: perceived discomfort, L4–L5 joint loading and typing/mousing productivity. Working in a sit–stand paradigm was found to have the potential to reduce discomfort when compared to working in a sitting or standing only configuration. Sit–stand was found to be associated with reduced lumbar flexion during sitting compared to sitting only. Increasing lumbar flexion during prolonged sitting is a known injury mechanism. Therefore, sit–stand exhibited a potentially beneficial response of reduced lumbar flexion that could have the potential to prevent injury. Sit–stand had no significant effect on productivity. Practitioner Summary: This study has contributed foundational elements to guide usage recommendations for sit–stand workstations. The sit–stand paradigm can reduce discomfort; however, working in a sit–stand ratio of 15:5 min may not be the most effective ratio. More frequent posture switches may be necessary to realise the full benefit of sit–stand.